Fabrication of Ginsenoside-Based Nanodrugs for Enhanced Antitumor Efficacy on Triple-Negative Breast Cancer - Zuo, Shuting; Wang, Jing; An, Xianquan; Wang, Zhenyu; Zheng, Xiao; Zhang, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
There is an urgent need to identify chemotherapeutic agents with improved efficacy and safety against triple-negative breast cancer (TNBC). Ginsenosides can reportedly induce tumor cell death, invasion, and metastasis; however, poor water solubility, low oral absorption rate, and rapid blood clearance limit their clinical application. Utilizing the amphiphilic property of ginsenosides as building blocks of biomaterials, we fabricated a carrier-free nanodrug composed of ginsenosides Rg3 and Rb1 using a nano-reprecipitation method without any additional carriers. After characterizing and demonstrating their uniform morphology and pH-sensitive drug release properties, we observed that Rg3-Rb1 nanoparticles (NPs) exhibited stronger antitumor and anti-invasive effects on TNBCs in vitro than those mediated by free ginsenosides. Consequently, Rg3-Rb1 NPs afforded superior inhibition of tumor growth and reduction of pulmonary metastasis than the Rg3 and Rb1 mixture, with no obvious systematic toxicity in vivo. Collectively, our results provide a proof-of-concept that self-assembled engineered ginsenoside nanodrugs may be efficient and safe for TNBC therapy.